Christian America? Secularized Evangelical Discourse and the Boundaries of National Belonging. (4th August 2018) - Delehanty, Jack; Edgell, Penny; Stewart, Evan
Abstract: Many scholars argue that evangelical Christian beliefs and traditions are central to dominant conceptions of American national identity, but most empirical studies in this area focus on the activities and identities of evangelical Christians themselves. Missing is an assessment of how evangelical-infused understandings of national belonging shape the views of people outside the white evangelical subculture. We analyze how Americans of all religious backgrounds evaluate a secularized evangelical discourse (SED)—a repertoire of political statements that are phrased in religiously nonparticularistic terms, but have roots in evangelical Christian history and epistemologies and have been politicized through social movements and party politics. Using latent class analysis and nationally representative survey data, we identify four prevailing profiles of support for claims about public religious expression anchored in this repertoire: ardent opposition, moderate opposition, moderate support, and ardent support. We find that a majority of Americans, not just evangelicals, respond positively to propositions that employ SED. Consequently, we argue that conservative Christianity influences contemporary politics not only by furnishing individuals with beliefs and identities, but also by providing a durable and flexible source of boundaries around a culturally specific vision of national belonging that resonates far beyond the boundaries of the evangelical subculture.